Early Experience with Low Profile Plate Osteosynthesis for Metacarpal Fractures - Joshi, A; K.C., BR; Chand, P; Thapa, BB (Journal of Nepal Health Research Council, 2009)
Background: Among various fixation methods for metacarpal fractures, plate osteosynthesis is the most rigid and allows early rehabilitation leading to early return to work. Many authors have reported high complication rates and most of them were because of thick plate. The aim of this study was to report early results of plate osteosynthesis of metacarpal fractures with low profile miniplate. Methods: This was a hospital based prospective study. Unstable and irreducible fractures were managed by open reduction and internal fixation with low profile miniplate and were followed up for 6 months. The functional outcome after fracture treatment was assessed by ability to perform acts of daily life and calculating American Society for Surgery of the Hand Total Active Flexion (ASSH TAF) score. Results: There were 16 patients with 17 metacarpal fractures, 87.5% were male with mean age of 31.50±9.02 years. Fourteen (87.5%) patients could perform their activities of daily living at four weeks. The mean Total Active Flexion was 261.76±24.87 at final follow up. Fourteen (87.5%) patients had excellent, one (6.25%) good and one (6.25%) poor out come at the end of 6 months. Conclusion: Low severity metacarpal fractures can be treated successfully by open reduction internal fixation with low-profile miniplate, allowing early and safe mobilization. Key words: low-profile plate, metacarpal fractures, plate osteosynthesis   DOI: 10.3126/jnhrc.v7i1.2274 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 19-24